2018
DOI: 10.1080/13552600.2018.1509575
|View full text |Cite
|
Sign up to set email alerts
|

A prison-model of CoSA: the potential to offer “through the gate” support and accountability

Abstract: Circles of Support and Accountability (CoSA) are an intervention used to support and enable those who have been convicted of a sexual offence (core member), to reintegrate back into society, whilst still holding them accountable for their behaviour (Cesaroni, 2001). The purpose of this study was to introduce a new prison-model of CoSA and to explore the core members' perceptions of their release from prison, and subsequent future in the community, prior to it starting. Interviews and repertory grids were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The first theme within the context of ambiguous practice involved a belief that the 'real job' of a volunteer involved more instrumental and practical support, which could not be started until the Core Member was released from prison. The importance of expressive and emotional support needs to therefore be reinforced to volunteers, along with the benefits of the prison sessions, which has been discussed in previous studies (Kitson-Boyce et al, 2018b, Kitson-Boyce et al, 2018c. Volunteer commitment was also raised as a potential issue by both the Core Members and the volunteers themselves.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The first theme within the context of ambiguous practice involved a belief that the 'real job' of a volunteer involved more instrumental and practical support, which could not be started until the Core Member was released from prison. The importance of expressive and emotional support needs to therefore be reinforced to volunteers, along with the benefits of the prison sessions, which has been discussed in previous studies (Kitson-Boyce et al, 2018b, Kitson-Boyce et al, 2018c. Volunteer commitment was also raised as a potential issue by both the Core Members and the volunteers themselves.…”
Section: Resultsmentioning
confidence: 98%
“…The volunteers seem eager to reach the community part of the CoSA. It is therefore, important for CoSA coordinators to recognise these feelings within volunteers and reinforce the benefits of the prison sessions that have been outlined previously (Kitson-Boyce et al, 2018b, Kitson-Boyce et al, 2018c).…”
Section: Extractmentioning
confidence: 98%
“…Research on peer mentorship programs in the context of the criminal legal system has demonstrated immense benefits, including improved health outcomes ( South et al , 2014 ; Cunningham et al , 2018 ; McLeod et al , 2019 ), feelings of belonging ( Collica, 2010 ; Fels et al , 2014 ; South et al , 2016 ) and connection with employment and disability services ( Hunter and Boyce, 2009 ; Redcross et al , 2016 ; Harrod, 2019 ). For many people, release can mean feelings of stress and hopelessness ( Kitson-Boyce et al , 2018 ; Liem and Weggemans, 2018 ; McLeod et al , 2020 ), peers are uniquely positioned to walk alongside people in offering comfort, wisdom and support.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is for volunteers from the local community to support and encourage their reintegration back into society, whilst still holding them accountable for their behavior (Cesaroni, 2002). The UK prison-model CoSA starts approximately 3 months prior to the Core Member's release from prison and lasts into the community on release, with the same volunteers for continuity of support (Kitson-Boyce, Blagden, Winder & Dillon, 2018a, 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…Keith agreed to complete the repertory grids as part of a larger research study exploring the experience of being involved in the prison-model CoSA (Kitson-Boyce et al, 2018a, 2018b.…”
Section: Introductionmentioning
confidence: 99%